BIROKRASI PROGRAM USAHA EKONOMI DESA - Arlis '; Mayarni ' (Universitas Riau, 2013)
The purpose of this study is toinvestigate and analyze the factors that influence the bureaucracy UED program - SP VillageBayur Island District Cerenti Singingi Kuantan District. Population and sample in this study wasthe managing UED, the verification team, the audit team and the facilitators and the community ofusers. Data was collected through questionnaire dissemination techniques, interviews andobservations, once the data is collected and then analyzed using qualitative and quantitativedescriptive analysis. Results showed bureaucracy UED program - SP Village Bayur Island DistrictCerenti Kuantan District Singingi still runs poorly. The dominant factor influencing bureaucraticUED-SP program performing its duties is the fear factor.